In vitro cytoprotective and in vivo anti-oral mucositis effects of melatonin and its derivatives - Mahakunakorn, Pramote; Sangchart, Pimpichaya; Panyatip, Panyada; Ratha, Juthamat; Damrongrungruang, Teerasak; Priprem, Aroonsri; Puthongking, Ploenthip (PeerJ, 2024)
According to our preliminary study, melatonin and its N-amide derivatives (N-(2-(1-4-bromobenzoyl-5-methoxy-1H-indol-3-yl)ethyl)acetamide (BBM) and 4-bromo-N-(2-(5-methoxy-1H-indol-3-yl)ethyl)benzamide (EBM)) inhibited the marker of acute inflammation in tests in vitro and in vivo. The anti-inflammatory agent is intended for the prevention and treatment of chemotherapy-induced toxicity. In this study aimed to evaluate the effect of melatonin and its derivatives on mechanisms related to chemotherapy-induced oral mucositis by in vitro ROS and 5-FU-induced human keratinocyte cells as well as in vivo oral mucositis model. In in vitro H2O2-induced HaCaT cells, BBM had the highest level of protection (34.57%) at a concentration 50 µM, followed by EBM (26.41%), and melatonin (7.9%). BBM also protected cells against 5-FU-induced to 37.69–27.25% at 12.5–100 µM while EBM was 36.93–29.33% and melatonin was 22.5–11.39%. In in vivo 5-FU-induced oral mucositis in mice, melatonin, BBM, and EBM gel formulations protected tissue damage from 5-FU similar to the standard compound, benzydamine. Moreover, the weight of mice and food consumption recovered more quickly in the BBM group. These findings suggested that it was possible to develop BBM and EBM as new therapeutic agents for the treatment of oral mucositis.
Keywords: Melatonin; Amide derivatives; 5-Fluorouracil; Oral mucositis; Chemotherapy; Cytoprotective